Temporal Relationship Between Particulate Matter (PM10) And Carbon Monoxide (CO) In Kuala Lumpur - Ghazali, Nurul Adyani (Universiti Sains Malaysia, 2005)
Air pollution is now becoming a common feature in Kuala Lumpur city. It has assumed an important level to the proportion that the city populace recognises its presence. The future of air pollution in the city seems to be bleak. From one stand point, air pollution although dangerous and threatening to the quality of life and environment, it is a luxurious problem and relatively remote in priority to the general public. This research is carried out to understand the changes in trend of particulate matter (PM10) and carbon monoxide (CO) concentration within a set time frame or limit in the selected monitoring sites which is located in heavily trafficked urban area of Malaysia which is Kuala Lumpur. Hourly and daily concentration of particulate matter and carbon monoxide are collected over an 8-month period from January to August. By using the statistical and graphical analysis, the data will be analysed and as the results, the variation of concentration for both particulate matter (PM10) and carbon monoxide (CO) will be define from the analysis. From the research, the results shows that the ambient level of carbon monoxide was relatively low as compared to the particulate matter. Based on the analysis, it was found that the annual average CO value is 2.52 ug/m3 while the annual average PM10 value is 77.64 ug/m3. It was shows that average PM10 levels in Kuala Lumpur network are generally higher than average CO levels. The concentrations levels of CO were far below the maximum limit of 30 ppm for one hour averaging time set by the Malaysian Guidelines. On the other hand, the PM10 mean concentration was higher but still not exceed the maximum limit 150 ug/m3 for the 24 hour averaging time which also set by the Malaysian Guidelines.